Potential of nitrogen management strategies to mitigate nitrous oxide emissions in corn - Lynn, Brett A. (Kansas State University, 2019)
Effective management of nitrogen (N) in corn (Zea mays L.) cropping systems can positively affect production and mitigate environmental impacts such as nitrous (N₂O) emissions. The goal was to quantify N₂O emissions and the response of corn to application of N employing diverse management approaches (soil test and sensor-based approaches) to identify effective N management strategies. In 2016 and 2017, a corn study was established on a Belvue silt loam soil at the Ashland Bottoms Research Farm south of Manhattan, KS (39º 08’ N lat, 96º 37’ W long). In 2017, an additional site on a Eudora silt loam was added at the Kansas River Valley Experiment Field northwest of Topeka, KS (39º 04’ N lat, 95º 46’ W long). The study was a randomized complete block design comprised of five treatments replicated four times. Nitrogen treatments were stream applied as 28% N in the form of urea ammonium nitrate and included: Check, Soil Test, Split-Soil Test, Sensor, and Aerial NDVI. Nitrous oxide emissions were measured throughout the growing season using a static chamber method. Cumulative emissions ranged between 0.03 – 0.14 kg N₂O-N ha⁻¹. There were no significant differences among treatment cumulative emissions at any of the three site-years. Manhattan grain yields ranged from 6.2 – 11.3 and 1.9 – 6.7 Mg ha⁻¹ in 2016 and 2017, respectively. Yield was not significantly across the four N management strategies in 2016, but in 2017 Split-Soil Test was significantly higher than Sensor. Topeka grain yields ranged from 8.0 – 15.2 Mg ha⁻¹. Soil Test and Split-Soil Test were significantly higher than Sensor and Aerial NDVI. Treatments receiving nitrogen yielded higher than the Check for all site-years. Yield-scaled nitrous oxide emissions (YSNE) were not significantly different at Manhattan in 2016 and Topeka in 2017. Check was significantly higher than the N management strategies at Manhattan in 2017. Emissions factor (EF) was ≥0.07 percent for all site-years on continuously tilled, low organic matter, river bottom silt loam soils with surface applied N fertilizer at agronomic N rates, which is markedly lower than the IPCC default value of one percent. Results between site-years were variable, which may stem from differences in site characteristics and water availability. Further investigation is needed to assess the ability of N management strategies to increase corn yield and lower N₂O emissions.
Keywords: Soil; Fertility; Nitrogen; Corn; Management; Rate